PENGARUH EDUKASI GIZI BERBASIS INSTAGRAM DAN ZOOM MEETING TERHADAP PENGETAHUAN DAN SIKAP TENTANG 1000 HARI PERTAMA KEHIDUPAN (1000 HPK) PADA REMAJA USIA 13-18 TAHUN DI KABUPATEN LAMONGAN - Al-Fadhilah, Amelia Ilmi (Jurnal Gizi dan Kesehatan Nusantara, 2023)
The nutritional status of adolescents will affect readiness during conception which will have an impact on the life cycle and long-term disturbances in the golden period of growth and development, namely in the first 1000 days of life from pregnancy until the child is 2 years old. Social media is a social networking site that is now widely used, especially among teenagers. The purpose of this study was to determine the effect of nutrition education through Instagram social media and zoom meetings and to analyze the differences in nutrition education through Instagram and zoom meetings on adolescents' mastery of knowledge and attitudes about the First 1000 Days of Life. The study used a quasy experimental design method with a one group pretest posttest research design. The sampling technique used purposive sampling so that 100 respondents were divided into 2 groups, namely the Instagram group and zoom meeting. From the results of the paired sample t-test, the results showed that nutrition education through Instagram and zoom meetings had an effect on adolescents' mastery of knowledge and attitudes. From the results of the independent t-test the difference between the two media shows that there are differences in the results of the knowledge of the Instagram and zoom meeting groups, but there are no differences in the results of attitudes in the two groupsKeywords: Instagram, Zoom meeting, the First 1000 Days of Life, teenagers.